Fikih Mubadalah and Its Challenges: A Study of Household Conflict Resolution in Lampung Province - Hilmi Yusron Rofi'i; Abd Qohar; Ahmad Khudlori; A Muslimin (Journal of Islamic Mubadalah, 2024)
This article is about the method of resolving conflict in the household through the application of mubadalah jurisprudence. The household conflict in question is like inequality in the division of tasks and responsibilities, as well as the lack of balance in decision-making which often becomes a source of disputes between husband and wife. The formulation of the problem in this article is how mubadalah jurisprudence can be applied as a solution to resolving household conflict and what are the obstacles faced in its implementation. The method used is qualitative with a phenomenological approach. Primary data was obtained through in-depth interviews with married couples who face conflict, community leaders, and family consultants. The location of the research was carried out in urban and rural areas in Lampung Province, Indonesia. Data analysis was carried out using the mubadalah theory which emphasizes the principle of mutuality in husband and wife relations. The results of the study indicate that the application of the mubadalah concept can be an effective solution in reducing household conflict, mubadalah prioritizes a more balanced husband and wife relationship. However, obstacles in implementing this principle include the strong patriarchal cultural factor and the weakness of society regarding the principles of mubadalah. The practical contribution of this research is to the understanding of society and institutions implementing Islamic law, such as the Religious Court and the Office of Religious Affairs, when making peace efforts or fostering the bride and groom to understand the importance of the principles of mubadalah.